SP3.2.12 Do the National Emergency Laparotomy Audit (NELA) performance indicators correlate with mortality? A retrospective analysis of years 4-6. (28th October 2021) - Dick, Lachlan; Tucker, Stefan; Bairstow, Fiona; Green, James; Young, Jamie
Abstract: Aims: Emergency laparotomy continues to carry significant morbidity and mortality. The National Emergency Laparotomy Audit (NELA) publishes individual hospital reports, detailing key performance indicators. We aimed to determine the impact of performance indicators on mortality. Methods: NELA aggregate hospital reports from years 4 to 6 were used to extract data relevant to the study aims. Linear regression was used to determine if any of the reported variables could be used as predictors of mortality. Results: An analysis of 559 hospital aggregates, totalling 73075 laparotomies was carried out. Overall, the average rate of mortality was 9.6%. There was no significant correlation between mortality with any common variable across years 4-6 data, including risk documentation before surgery, arrival in theatre appropriate to urgency, consultant review preoperatively and supervision in theatre, admission to critical care, care of the elderly assessment, unplanned return to theatre or admission to critical care and length of stay. Conclusion: No single performance indicator alone appears to correlate significantly with mortality. Multivariable analysis may identify some performance indicators, however, given that across all the hospitals there is a high standard of performance for each of the reported variables, the variation in mortality is likely influenced by other factors not evaluated by the hospital aggregate reports.